"All this universe is perfused with signs": the nostalgia of sentient others, (bio)semiosis, and SF. Issue 3 (2nd July 2020) - Hope, Jonathan
ABSTRACT: Where are other minds? What networks of communication keep them together and enable us to connect? I will address these questions in the following pages by relying on philosophical essays and works of SF (science fiction/speculative fiction). More precisely, I propose to associate the imaginary worlds in Frank Herbert's renowned novel Dune and those in Les Naufragés du Temps, a series of bandes dessinées (comics) authored by Paul Gillon and Jean-Claude Forest, with the semiotics of Charles Sanders Peirce and Barbara Cassin's recent reflections on translatability and nostalgia. The objective is to question – and maybe provoke, welcome – a nostalgic desire for languages or webs of meaning, whatever their nature.